Analisis Faktor-Faktor yang Mempengaruhi Tingkat Produksi - Joice Machmud; Umar Sako Baderan; Zulkarnain Suronoto; Mohamad Ilyas Abas (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine and analyze whether: 1) land area has a partial and significant effect on rice production yields, 2) Fertilizer (urea) has a partial and significant effect on rice production, 3) Seeds have a partial and significant effect on rice production, 4) Pesticides have a partial and significant effect on rice production, and 5) Land area, fertilizer (urea), seeds and pesticides have a simultaneous and significant effect on rice production in Paris Village, Mootilango District. The research method used is a type of research with a descriptive quantitative approach. The results of the study were: 1) The results of farmers' rice production in Paris Village, Mootilango District, Gorontalo Regency of 74.80 percent were influenced by land area factors (X1), Urea factor (X2), Seed Factor (X3) and Pesticide factor (X4), 2) Partially the land area factor of Seed factor (X3) has a positive and significant effect on the amount of rice production produced by farmers in Paris Village, Mootilango District, Gorontalo Regency. Meanwhile, the land area factor (X1), Urea factor (X2), and Pesticide factor (X4) did not have a positive and significant effect on the amount of rice production produced by farmers in Paris Village, Mootilango District, Gorontalo Regency, and 3) Simultaneously the land area factor (X1), Urea factor (X2), seed factor (X3) and Pesticide factor (X4) positively and significantly affect the amount of rice production produced by farmers in Paris Village, Mootilango District, Regency Gorontalo.